Acetylated Signal Transducer and Activator of Transcription 3 Functions as Molecular Adaptor Independent of Transcriptional Activity During Human Cardiogenesis. (31st July 2017) - Mehta, Ashish; Ramachandra, Chrishan J. A.; Chitre, Anuja; Singh, Pritpal; Lua, Chong Hui; Shim, Winston
Abstract : Activation of signal transducer and activator of transcription 3 (STAT3) is imperative for mammalian development, specifically cardiogenesis. STAT3 phosphorylation and acetylation are key post-translational modifications that regulate its transcriptional activity. Significance of such modifications during human cardiogenesis remains elusive. Using human pluripotent stem cells to recapitulate cardiogenesis, two independently modified STAT3α (92 kDa) isoforms (phosphorylated and acetylated), which perform divergent functions were identified during cardiomyocyte (CM) formation. Phosphorylated STAT3α functioned as the canonical transcriptional activator, while acetylated STAT3α underwent caspase-3-mediated cleavage to generate a novel STAT3ζ fragment (∼45 kDa), which acted as a molecular adaptor integral to the ErbB4-p38γ signaling cascade in driving CM formation. While STAT3α knockdown perturbed cardiogenesis by eliminating both post-translationally modified STAT3α isoforms, caspase-3 knockdown specifically abrogates the function of acetylated STAT3α, resulting in limited STAT3ζ formation thereby preventing nuclear translocation of key cardiac transcription factor Nkx2-5 that disrupted CM formation. Our findings show the coexistence of two post-translationally modified STAT3α isoforms with distinct functions and define a new role for STAT3 as a molecular adaptor that functions independently of its canonical transcriptional activity during human cardiogenesis.